Dysregulation of Vascular Endothelial Progenitor Cells Lung-Homing in Subjects with COPD. (12th May 2016) - Salter, Brittany M.; Manzoor, Fizza; Beaudin, Suzanne; Kjarsgaard, Melanie; Nair, Parameswaran; Gauvreau, Gail M.; Sehmi, Roma
Abstract : Chronic obstructive pulmonary disease (COPD) is characterized by fixed airflow limitation and progressive decline of lung function and punctuated by occasional exacerbations. The disease pathogenesis may involve activation of the bone marrow stimulating mobilization and lung-homing of progenitor cells. We investigated the hypothesis that lower circulating numbers of vascular endothelial progenitor cells (VEPCs) are a consequence of increased lung-sequestration in COPD. Nonatopic, current or ex-smokers with diagnosed COPD and nonatopic, nonsmoking normal controls were enrolled. Blood and induced sputum extracted primitive hemopoietic progenitors (HPCs) and VEPC were enumerated by flow cytometry. Migration and adhesive responses to fibronectin were assessed. In sputum, VEPC numbers were significantly greater in COPD compared to normal controls. In blood, VEPCs were significantly lower in COPD versus normal controls. There were no differences in HPC levels between the two groups in either compartment. Functionally, there was a greater migrational responsiveness of progenitors from COPD subjects to stromal cell-derived factor-1alpha (SDF-1 α ) compared to normal controls. This was associated with greater numbers of CXCR4 + progenitors in sputum from COPD. Increased migrational responsiveness of progenitor cells may promote lung-homing of VEPC in COPD which may disrupt maintenance and repair of the airways and contribute to COPD disease pathogenesis.